Strategy to Increase Community Participation in Regional Tax Payment through the Use of Social Media at Bapenda Surabaya - Junior, Hanny Naafillia; Fadil, Cholid; Imaningsih, Niniek (Unram Journal of Community Service, 2025)
This study aims to explore strategies to increase community participation in regional tax payments through the use of social media by the Surabaya Regional Revenue Agency (Bapenda). Local taxes are one of the important sources of revenue for local governments, and increasing public participation is essential for sustainable urban development. Social media, with its wide reach, real-time interactions, and engaging content, provides an effective communication tool to increase public awareness and participation. This study uses a qualitative approach with a case study method to research Bapenda's strategy, the challenges faced, and the effectiveness of the use of social media in tax education. Data collection was carried out through in-depth interviews with key informants, participatory observations, and documentation of Bapenda's social media activities. The results of the study show that Bapenda Surabaya utilizes platforms such as Facebook, Instagram, and Twitter to disseminate various content, such as infographics, educational videos, and payment reminders, to engage the public. Social media has proven to be effective in reaching a wider audience, especially the younger generation, although there are still challenges in terms of accessibility for older age groups and people who are less familiar with digital platforms. The study also identified key obstacles, such as resource constraints, technical challenges, and community skepticism. Recommendations for improvement include the use of simpler language, expanding the use of traditional media along with digital platforms, and increasing transparency regarding the use of tax funds. This research contributes to understanding how social media can be used to increase participation in local tax payments, which in turn supports the development of the city of Surabaya